DIGITAL STORYTELLING AS A METHOD FOR ENHANCING ORAL COMMUNICATION SKILLS IN FOREIGN LANGUAGE TEACHING - Talapova A. K.; Nurgali N. N. (World Scientific Reports, 2024)
This article examines the impact of digital storytelling on enhancing oral communication skills in foreign language teaching. With the increasing demand for more effective language acquisition methods, digital storytelling has emerged as a powerful tool for improving speaking proficiency. Combining multimedia elements—text, images, audio, and video—this approach offers students an interactive and creative learning experience that enhances vocabulary, pronunciation. The study explores how digital storytelling promotes collaboration, allowing students to share their stories, receive feedback, and actively engage in their learning process. Digital storytelling connects students with real-world narratives, fostering critical thinking, cultural understanding, and engagement. Surveys reveal improved creativity but highlight challenges like technical barriers and teacher support. Despite these issues, it holds great potential for enhancing speaking skills in language education, with solutions proposed for better implementation.